2010
DOI: 10.1016/j.bbmt.2010.01.017
|View full text |Cite
|
Sign up to set email alerts
|

Oral Symptom Intensity, Health-Related Quality of Life, and Correlative Salivary Cytokines in Adult Survivors of Hematopoietic Stem Cell Transplantation with Oral Chronic Graft-versus-Host Disease

Abstract: Oral chronic graft-versus-host disease (cGVHD) is a frequent, clinically significant sequela of allogeneic hematopoietic stem cell transplant (HSCT). This study was designed to elucidate relationships among clinical characteristics of oral cGVHD and related oral pain and oral dryness, salivary proinflammatory cytokine IL6 and IL1α concentrations, and health-related quality of life (HRQL). An understanding of the characteristics and correlates of oral cGVHD manifestations and related symptoms such as dryness is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
50
1
5

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(58 citation statements)
references
References 49 publications
2
50
1
5
Order By: Relevance
“…Only a minority, 15% (n ¼ 13), complained that xerostomia adversely impacted on their quality of life. This finding, in contrast to recent studies showing that moderate to severe xerostomia was associated with the poorest levels of overall health-related quality of life, 19 is difficult to explain but may relate to differences in measures used to assess xerostomia and quality of life.…”
Section: Oral Sites Involvedcontrasting
confidence: 55%
“…Only a minority, 15% (n ¼ 13), complained that xerostomia adversely impacted on their quality of life. This finding, in contrast to recent studies showing that moderate to severe xerostomia was associated with the poorest levels of overall health-related quality of life, 19 is difficult to explain but may relate to differences in measures used to assess xerostomia and quality of life.…”
Section: Oral Sites Involvedcontrasting
confidence: 55%
“…Oral cGVHD has also been associated with altered taste and intolerance for spicy and acidic foods (Schubert and Correa, 2008). Oral dryness is consistently associated with poor quality of life (Fall-Dickson et al, 2010). In this study, patients with oral cGVHD reported having higher Lee Symptoms Scale bother scores from avoidance of foods as well as from ulcerations and also reported having greater mouth pain and sensitivity as compared with patients without oral cGVHD.…”
Section: Discussionmentioning
confidence: 91%
“…Studies have shown that immunological mechanisms of cGVHD include donor-derived alloreactive T lymphocytes, autoreactive T lymphocytes and regulatory T lymphocytes as well as the dysregulation of cytokine expression [13]. The first grading scheme for the severity of systemic cGVHD was proposed in 1980 based on data from 20 subjects classifying the disease as limited when it affects skin and/or liver or as extensive when present skin involvement or localized skin involvement or hepatic dysfunction caused by chronic GVDH in combination with histological changes of the liver that showed chronic aggressive hepatitis, bridging necrosis or cirrhosis, involvement of the eye, histologically proven involvement of minor salivary glands or oral mucosa on labial biopsy, or proven involvements of any other target organ [5].…”
Section: Discussionmentioning
confidence: 99%